2011
DOI: 10.1093/restud/rdq003
|View full text |Cite
|
Sign up to set email alerts
|

Consumption Inequality and Intra-household Allocations

Abstract: The consumption literature uses adult equivalence scales to measure individual level inequality. This practice imposes the assumption that there is no within household inequality. In this paper, we show that ignoring consumption inequality within households produces misleading estimates of inequality along two dimensions. First, the use of adult equivalence scales underestimates the level of cross sectional consumption inequality by 30%. This result is driven by the fact that large differences in the earnings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(127 citation statements)
references
References 38 publications
5
109
0
2
Order By: Relevance
“…In the US, Europe, and Australia, studies have consistently shown that for women the risk of obesity is 20 per cent to 40 per cent higher among individuals who are food insecure (Burns 2004, 15). An intra-household inequalities lens provides strong challenges to a household unity that models a behaviour of equal consumption (Lise and Seitz 2011) and equitable sharing of resources between two adults. For our research, intrahousehold inequalities were visible.…”
Section: Nutrition Transitions Health Inequalities and 'Fall-back Pmentioning
confidence: 99%
“…In the US, Europe, and Australia, studies have consistently shown that for women the risk of obesity is 20 per cent to 40 per cent higher among individuals who are food insecure (Burns 2004, 15). An intra-household inequalities lens provides strong challenges to a household unity that models a behaviour of equal consumption (Lise and Seitz 2011) and equitable sharing of resources between two adults. For our research, intrahousehold inequalities were visible.…”
Section: Nutrition Transitions Health Inequalities and 'Fall-back Pmentioning
confidence: 99%
“…These numbers indicate that 11.5 % of total inequality among women and men living in couple households arises from within household inequality. Other authors report even higher proportions, e.g., Bii'TIKOFER andGERFIN (2017) find 16% andLISE and estimate that 25% is due to within household inequality.…”
Section: Consumption Inequalitymentioning
confidence: 94%
“…& shown by LISE and SEITZ (2011), inequality is likely to be underestimated when ignoring within-household inequality. In this section, inequality measures are computed for couple households, widows and widowers.…”
Section: Consumption Inequalitymentioning
confidence: 99%
“…The resulting picture may be quite different from reality. Recently, Lise and Seitz (), using British data, have provided estimates of intra‐household inequality and its evolution over several decades. Their conclusion is twofold.…”
Section: Equivalence Scales: the Current Situationmentioning
confidence: 99%